AN ERROR ANALYSIS OF REGULAR AND IRREGULAR VERBS IN WRITING RECOUNT, NARRATIVE, PROCEDURE AND DESCRIPTIVE TEXT BY THE TENTH GRADE STUDENTS AT SMA NEGERI 2 TANJUNGBALAI - Roselina Sitepu and Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This research deals with an error analysis. The objectives of the study are (1) to identify and classify the kinds of regular and irregular verbs error find in recount, narrative, procedure, and descriptive writing by the tenth grade students at SMA Negeri 2 Tanjungbalai, (2) to know the most dominant text getting regular and irregular verbs error by the tenth grade students at SMA Negeri 2 Tanjungbalai, (3) to find out the causes of regular and irregular verbs error in recount, narrative, procedure, and descriptive writing by the tenth grade students at SMA Negeri 2 Tanjungbalai. The research design that was used in this study is descriptive research. The sources of data were taken from the tenth grade students of SMA Negeri 2 Tanjungbalai which consists of 40 students who were chosen by taking the X-2 class as the sample. In this research, the writing text was used as collecting data. The result of the analysis shows that: (1) the errors of regular and irregular verbs in recount, narrative, procedure, and descriptive writing made by the tenth grade students of SMA Negeri 2 Tanjungbalai were 112 occurrences of all errors. The most dominant text getting regular and irregular verbs was narrative text occurred 40 cases (10 regular verbs and 30 irregular) or (36%), it was followed by recount text occurred 36 cases (7 regular verbs and 29 irregular verbs) or (32%) then the descriptive text occurred 26 cases (7 regular verbs and 19 irregular verbs) or (23%) and the last was Procedure text occurred 10 cases (2 regular verbs and 8 irregular verbs) or (8%).